Médiation de concepts avec la nouvelle méthode de français : C’est parti ! - Chmiel-Bożek, Halina (Neofilolog, 2021)
The concept of mediation in foreign language teaching and learning is becoming increasingly present in literature, but due to the evolving nature of this term, many studies do not include all of its aspects. Since the publication of Common European Framework of Reference for Languages in 2001, the notion of mediation has been considerably developed and the scope of mediation activities has been extended. This article is devoted to the term “mediating concepts”, which is used in Companion Volume from 2018, which updates the CEFR 2001. On the basis of the latest studies, we would like to discover what is understood by the latest idea of “mediating concepts” and what are the practical applications of these theoretical considerations, using the example of a new method of teaching French: C’est parti!